Possis: predicting spectra, light curves, and polarization for multidimensional models of supernovae and kilonovae. Issue 4 (7th September 2019) - Bulla, M
ABSTRACT: We present possis, a time-dependent three-dimensional Monte Carlo code for modelling radiation transport in supernovae and kilonovae. The code incorporates wavelength- and time-dependent opacities, and predicts viewing-angle dependent spectra, light curves, and polarization for both idealized and hydrodynamical explosion models. We apply the code to a kilonova model with two distinct ejecta components, one including lanthanide elements with relatively high opacities and the other devoid of lanthanides and characterized by lower opacities. We find that a model with total ejecta mass $M_ej=0.04\, M_\odot$ and half-opening angle of the lanthanide-rich component Φ = 30° provides a good match to GW 170817/AT 2017gfo for orientations near the polar axis (i.e. for a system viewed close to face-on). We then show how crucial is the use of self-consistent multidimensional models in place of combining one-dimensional models to infer important parameters, such as the ejecta masses. We finally explore the impact of M ej and Φ on the synthetic observables and highlight how the relatively fast computation times of possis make it well-suited to perform parameter-space studies and extract key properties of supernovae and kilonovae. Spectra calculated with possis in this and future studies will be made publicly available.